2015
DOI: 10.4236/fns.2015.615143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Hydroponic and Soil-Grown Strawberries: Sensory Attributes and Correlations with Nutrient Content

Abstract: Hydroponic growing methods are growing in popularity and seem to have numerous benefits (i.e., environmental, increased product yields, year round growing) compared to soil grown crops. Although these advantages are attractive, they do not guarantee a high quality product. Taste is a driver of consumer acceptance; therefore, sensory analysis of the hydroponic product will be an important indicator in its success. In this study, we evaluated the sensory differences and preferences in hydroponically grown and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…It has been reported that hydroponic culture increased vitamin C, flavone, nitrate contents, and yield of sweet potato leaves compared with soil culture (Chen et al, 2013). In the previous study, compared to soil grown strawberries, the hydroponically grown strawberries were wined preferred by 70% of participants in the sensory analysis (Treftz et al, 2015). We also found that hydroponic culture also can effectively improve the taste quality in leafy sweet potato, especially the cultivars with poor taste under soil culture in the field.…”
Section: Introductionmentioning
confidence: 52%
“…It has been reported that hydroponic culture increased vitamin C, flavone, nitrate contents, and yield of sweet potato leaves compared with soil culture (Chen et al, 2013). In the previous study, compared to soil grown strawberries, the hydroponically grown strawberries were wined preferred by 70% of participants in the sensory analysis (Treftz et al, 2015). We also found that hydroponic culture also can effectively improve the taste quality in leafy sweet potato, especially the cultivars with poor taste under soil culture in the field.…”
Section: Introductionmentioning
confidence: 52%
“…Compared to production methods, variety had greater influence on sensory attributes of tomatoes [28]. Similarly, Treftz et al [20] reported that sensory evaluation can be influenced by several factors such as genetic composition, pre-harvest factors (light, temperature, humidity, and wind) and post-harvest factors. Other influences include price, brand, and consumer mood, which affect the sensory evaluation of the product.…”
Section: Sensory Analysis Carried Out By the Evaluatorsmentioning
confidence: 99%
“…Hydroponically grown strawberries showed higher mean ratings for these two categories. Consequently, they reported that due to the environmental benefits of hydroponic production combined with the favorable ratings of descriptive sensory analysis, it may be desirable for the consumer and beneficial for the environment to grow strawberry varieties in infertile areas to provide fresh fruit [20]. In 2011, a study was conducted to compare hydroponically, conventionally, and organically grown lettuces.…”
Section: Sensory Analysis Carried Out By the Evaluatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Albion frigo. Treftz et al [14] reported combined benefits of environment and better sensory attributes, and it is desirable to grow strawberry hydroponically. Treftz and Omaye [15] noted that growing strawberries in hydroponic systems are more sustainable and superior to soil grown systems.…”
Section: Work Donementioning
confidence: 99%